Evaluative Study: The Effectiveness Of Montesorri Method - Irdiyansyah, Iyan; Putrindi, Erien Gmelina (UNIVERSITAS PAKUAN, 2023)
This study reports a qualitative study using descriptive analytics method that finding out the effectiveness of Montessori Method for young learners. Montessori Method is a method that rarely used in Indonesia and there are only some of the schools that apply this method. Teachers who decide to work in the Montessori school basis should be ready with the challenges that might be appear when teaching children to learn using a specific method. The subjects of this research are Cita Harmoni Montessori Teacher. The data were collected through interview, observation and documentation. The study showed that teacher face several challenges when teaching using Montessori Method. Some children still unfamiliar with the Montessori Materials, got some difficulties in understanding abstract concepts even though they have used Montessori materials, children who are solitaire and is difficult to blend in group, some teachers who are not fully understand in working with Montessori Materials and the lack of maximum use of the Montessori apparatus in learning are the challenges that found in this study. In conclusion, teaching using a Montessori Method will be effective to be applied when the materials are involved and mastered. Additionally, it will be the challenge of Montessori teachers in the future.